(3eOGM GdCQhGM aj GdJUQjas - (3MSGe GdOjf CHh GdaVGFd CMeO Hf Ydj Hf eSYhO,J (B700 (3g` s ((3MGaX edG UGdM s)
(3ChdgG (B:s
(3bGd GdeaJbQ Edi Gddg GdhOhO GHf eSYhO EYde Cf GdUQa Ce GdYdhe hGdfMh CHhgG aLeYJ ajg cJGHkG ehShekG H` EYde Cf GdUQa jMJGL ai eYQaI GdChRGf Edi SHYI CHhGH s
(3BNQgG (B:s
(3hMce dGe gPg GdCTjGA cMce GdfGbU hai GdJi de jLJeY GdEYdGA dCf jchf McegG CjVkG cMce Whi fMh Whi Whjf hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ YfGhjf GdCHhGH hGdaUhd HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdUQas